LEGAL CONSEQUENCES OF VIOLATION OF THE DISTRIBUTION OF ABSOLUTE RIGHTS OR LEGITIME PORTIE WHICH RESULT IN INHERITANCE DISPUTES - Vianka, Maria Ibella; Gunadi, Ariawan (Awang Long Law Review, 2025)
A will deed is a legal document expressing the testator's final wishes and has binding legal force if created according to applicable law. In practice, inheritance disputes often arise when the contents of a will violate the heirs’ mandatory portion (legitime portie). Such violations can result in legal harm and lead to lawsuits against the notary as the official deed maker. This study aims to analyze the notary’s legal responsibility and the role of the Notary Supervisory Council in resolving inheritance disputes involving wills that breach legitime portie. The research method is normative juridical with a statutory and case approach. The findings show that a notary is obligated to provide legal counseling and refuse to draft deeds that contradict the law, including provisions on legitime portie under Article 913 of the Indonesian Civil Code. If a notary violates this obligation, they may be held civilly liable and sanctioned administratively by the Supervisory Council. The Notary Supervisory Council is authorized to examine notaries, impose sanctions, and report findings through a tiered system from local to national level. In many cases, this oversight mechanism is crucial in maintaining notarial professionalism and integrity while protecting the rights of disadvantaged heirs. It is concluded that the preventive and repressive role of the Notary Supervisory Council must be strengthened to prevent and resolve inheritance disputes arising from legitime portie violations by notaries.